Review of the process of accreditation of health institutions in the Region of Magallanes and Chilean Antarctica. - Silva Jiménez, Diego; Mendéz Celis, Paula; Vargas Olivares, Carolina; Lizondo Valencia, Romina (Universidad Tecnocientífica del Pacífico S.C., 2022)
The accreditation processes of health institutions ensure compliance with minimum standards to ensure patient safety. Objective: To review the accreditation process of health institutions in the Region of Magallanes and Chilean Antarctica. Materials and method Quantitative research, with a descriptive approach and a longitudinal-sectional design, through direct observation, the registry of accredited providers of closed care, of the Magallanes Region and the Chilean Antarctic of the Superintendency of Health, was reviewed. analyzing their accreditation processes of the five registered establishments of high medium and low complexity. Results: the five establishments were accredited in a timely and appropriate manner, obtaining 100% compliance with the mandatory characteristics. Conclusions The health institutions for their proper functioning must accredit periodically, which has been fulfilled in this region, however this is the beginning for an installation of the culture of health safety. Los procesos de acreditación de las instituciones sanitarias velan por el cumplimento de estándares mínimos para asegurar la seguridad el paciente. Objetivo: Revisar el proceso de acreditación de las instituciones sanitarias en la Región de Magallanes y Antártica Chilena. Materiales y el método Investigación de tipo cuantitativo, con enfoque descriptivo y diseño longitudinal, a través de observación directa, se revisó el registro de prestadores acreditados de atención cerrada, de la Región de Magallanes y Antártica Chilena de la Superintendencia de Salud, analizando sus procesos de acreditación de los cinco establecimientos registrados de alta mediana y baja complejidad. Resultados, los cinco establecimientos se acreditaron en tiempo y forma, obteniendo el 100% del cumplimiento de las características obligatorias. Conclusiones las instituciones sanitarias para su buen funcionamiento deben acreditar periódicamente, lo cual se cumplió en esta región sin embargo este es el comienzo para una instalación de la cultura de ...